2018
DOI: 10.1097/aln.0000000000002130
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation and Central Sensitization in Chronic and Widespread Pain

Abstract: Chronic pain is maintained in part by central sensitization, a phenomenon of synaptic plasticity, and increased neuronal responsiveness in central pain pathways after painful insults. Accumulating evidence suggests that central sensitization is also driven by neuroinflammation in the peripheral and central nervous system. A characteristic feature of neuroinflammation is the activation of glial cells, such as microglia and astrocytes, in the spinal cord and brain, leading to the release of proinflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
824
4
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 959 publications
(850 citation statements)
references
References 287 publications
(361 reference statements)
12
824
4
10
Order By: Relevance
“…23 Neuroinflammation has also been verified to function in visceral pain and chronic pain. 2 In our study, we found similar parallel changes in Nrg1-ErbB signaling, microglia status, and IL-1β expression in the SDH of the CYP-induced cystitis model. Neuroinflammation, which occurred at the spinal cord level, was shown to be attenuated by downregulation of Nrg1-ErbB signaling, leading to pain relief in the cystitis model.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…23 Neuroinflammation has also been verified to function in visceral pain and chronic pain. 2 In our study, we found similar parallel changes in Nrg1-ErbB signaling, microglia status, and IL-1β expression in the SDH of the CYP-induced cystitis model. Neuroinflammation, which occurred at the spinal cord level, was shown to be attenuated by downregulation of Nrg1-ErbB signaling, leading to pain relief in the cystitis model.…”
Section: Discussionsupporting
confidence: 81%
“…Further, bidirectional signaling between glial cells and neurons, which are important circuits in neuroinflammation, facilitates the development of persistent pain . Neuroinflammation has also been verified to function in visceral pain and chronic pain . In our study, we found similar parallel changes in Nrg1‐ErbB signaling, microglia status, and IL‐1β expression in the SDH of the CYP‐induced cystitis model.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…50,51 After nervous system injury, glial cell activation and the production of proinflammatory mediators, such as the pro-inflammatory cytokines IL-1β, IL-18, IL-6 y TNFα, can directly modulate the activity of neurons and other glial cells, contributing to the development and maintenance of chronic pain. 50,51 In fact, modulating the neuroinflammatory process has emerged as a promising option for the treatment of neuropathic pain. 51 Interestingly, in the recent years, neuroinflammation has been proposed as a major mechanism underlying CIPN-associated pain.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 In fact, modulating the neuroinflammatory process has emerged as a promising option for the treatment of neuropathic pain. 51 Interestingly, in the recent years, neuroinflammation has been proposed as a major mechanism underlying CIPN-associated pain. 10 In fact, we detected a significant increase in the mRNA levels of GFAP and Iba-1 (markers of satellite glial cells/astrocyes and microglila cells/macrophages, respectively), both in the lumbar DRG and dorsal spinal cord of animals receiving OXA.…”
Section: Discussionmentioning
confidence: 99%